Global burden of trichomoniasis: current status, trends, and projections (1990–2021) - Xingmin Wei; Xingmin Wei; Lu Liu; Kun Liu; Xiaoang Qin; Jianjun Wu; Jianjun Wu; Lou Jiang; Longjian Shang (Frontiers in Public Health)
ObjectivesTrichomoniasis one of the most neglected sexually transmitted diseases (STDs), imposes a significant global disease burden. This study aims to assess the burden and trends of trichomoniasis from 1990 to 2021 and to project its incidence from 2022 to 2050.MethodsThis study utilized data from the Global Burden of Disease 2021 study for secondary analysis. We determined the age-standardized incidence rate (ASIR) and disability-adjusted life years (DALYs) of trichomoniasis by sex, age, and socio-demographic index (SDI) level. Changes in burden trends across sex and age were explored from 1990 to 2021, using joinpoint regression. The incidence of trichomoniasis was projected for the period 2022 to 2050, using R software.ResultsFrom 1990 to 2021, the estimated annual percentage change (EAPC) in the global ASIR of trichomoniasis was 0.09 (95% CI: 0.06 to 0.13). In 2021, the global ASIR of trichomoniasis was 4,133.41 per 100,000 people (95% UI: 3,111.37 to 5,583.56 per 100,000). By population group, the ASIR was higher in men (4,353.43 per 100,000) than in women (3,921.31 per 100,000) in 2021, while the DALY rate was significantly higher in women than in men (6.45 vs. 0.23 per 100,000). When divided by age groups, the trend in ASIR among women aged 30–54 years aligned closely with the overall population incidence trend. In 2021, ASIRs were highest in low SDI regions, and the projected ASIRs by 2050 are 5,680.57 per 100,000 in males and 5,749.47 per 100,000 in females.ConclusionTrichomoniasis represents a significant global disease burden, particularly among women in low-income areas and individuals aged 30–54 years. The study highlights the need for targeted strategies to reduce the burden of trichomoniasis-related infections, especially in vulnerable populations.